2012
DOI: 10.1124/jpet.112.194761
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Supraspinal Histamine H3 Receptors Modulates Spinal Neuronal Activity in Neuropathic Rats

Abstract: There is growing evidence supporting a role for histamine H 3 receptors in the modulation of pathological pain. To further our understanding of this modulation, we examined the effects of a selective H 3 receptor antagonist, 6-((3-cyclobutyl-2,3,4,5-tetrahydro-1H-3-benzazepin-7-yl)oxy)-N-methyl-3-pyridinecarboxamide (GSK189254), on spinal neuronal activity in neuropathic (L5 and L6 ligations) and sham rats. Systemic administration of GSK189254 (0.03-1 mg/kg i.v.) dose-dependently decreased both evoked (10-g vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 56 publications
(102 reference statements)
4
21
0
1
Order By: Relevance
“…WDR neurons spontaneously fired at a higher rate in neuropathic rats compared with the uninjured animals and is consistent with previous reports (Chu et al 2004;McGaraughty et al 2009McGaraughty et al , 2012Suzuki and Dickenson 2006). An increased level of spontaneous discharge in WDR neurons following tissue or nerve injury indicates spinal hyperexcitability and may also suggest that there is stimulus-independent ongoing pain in these animals (Chu et al 2004;Suzuki and Dickenson 2006).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…WDR neurons spontaneously fired at a higher rate in neuropathic rats compared with the uninjured animals and is consistent with previous reports (Chu et al 2004;McGaraughty et al 2009McGaraughty et al , 2012Suzuki and Dickenson 2006). An increased level of spontaneous discharge in WDR neurons following tissue or nerve injury indicates spinal hyperexcitability and may also suggest that there is stimulus-independent ongoing pain in these animals (Chu et al 2004;Suzuki and Dickenson 2006).…”
Section: Discussionsupporting
confidence: 82%
“…The mean baseline spontaneous activity of WDR neurons in SNL rats was significantly higher (P Ͻ 0.01) than that in uninjured rats and is similar to levels reported previously (Chu et al 2004;McGaraughty et al 2012). C-fiber evoked responses were significantly elevated in SNL rats compared with the uninjured rats (P Ͻ 0.05); however, no other measure of evoked firing was different between the two groups.…”
Section: Baseline Activity Of Wdr Neuronssupporting
confidence: 75%
“…Moreover, Wei et al [5] reported that microinjection of A-960656, a histamine H 3 receptor antagonist, into the LC suppressed hypersensitivity in spinal nerve ligature model of neuropathic pain in rats. Additionally, microinjection of GSK189254 (a histamine H 3 receptor antagonist) into the LC reduced the evoked firing of wide dynamic range neurons in the spinal cord [32]. Although the distribution of histamine H 2 receptors in the ACC has not been reported, positron emission tomography (PET) revealed that cingulate cortex has a high density of histamine H 1 receptors [33].…”
Section: Discussionmentioning
confidence: 98%
“…Another two H3R antagonists, namely GSK-189254 and GSK-239512, have been described as potent, selective, and highly brain penetrant antagonists with proven effectiveness in a number of animal experiments, including attentional and memory models (Figure 10, Table 1) [53,59,[91][92][93][94][95][96][97]. Interestingly, GSK-239512 has completed phase 1 clinical trial, and the results suggest a modest efficacy in mild-moderate AD patients (ClinicalTrials.gov trial registration number: NCT00675090).…”
Section: Alzheimer's Diseasementioning
confidence: 94%